2009
DOI: 10.1603/029.102.0137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Powdery Mildew Fungicide Programs on Twospotted Spider Mite (Acari: Tetranychidae), Hop Aphid (Hemiptera: Aphididae), and Their Natural Enemies in Hop Yards

Abstract: Twospotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae), and hop aphid, Phorodon humuli (Schrank) (Hemiptera: Aphididae), are the most important arthropod pests of hop (Humulus lupulus L.) in the Northern Hemisphere. A potential barrier for greater adoption of conservation biological control strategies for spider mites and hop aphid is the extensive use of fungicides for management of hop powdery mildew, Podosphaera macularis (Wallr.:Fr.) U. Braun & S. Takamatsu. Field studies conducted in expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…These products are known to affect arthropods in general and natural enemies in particular so that could explain lower parasitism rates in organic vineyards (Nash et al, 2010). For instance, several studies have shown the negative effect of sulphur on a wide range of natural enemies including parasitoids, predatory mites and spiders (Gent et al, 2009;Martinson et al, 2001;Nash et al, 2010). Our findings suggest the need for a more detailed description of farming systems to provide a more mechanistic understanding of the way farming systems shape ecological processes such as biological control of pests (Puech et al, 2014;Rusch et al, 2011).…”
Section: Variablesmentioning
confidence: 80%
“…These products are known to affect arthropods in general and natural enemies in particular so that could explain lower parasitism rates in organic vineyards (Nash et al, 2010). For instance, several studies have shown the negative effect of sulphur on a wide range of natural enemies including parasitoids, predatory mites and spiders (Gent et al, 2009;Martinson et al, 2001;Nash et al, 2010). Our findings suggest the need for a more detailed description of farming systems to provide a more mechanistic understanding of the way farming systems shape ecological processes such as biological control of pests (Puech et al, 2014;Rusch et al, 2011).…”
Section: Variablesmentioning
confidence: 80%
“…Commercial deployment of MeSA dispensers could potentially replace one or more miticide applications, therefore we tested a lower rate (123/ha) that is near the typical cost of a single miticide application (approximately $120US/ha). Deployment in both years was timed to coincide with the natural occurrence of pest species, and corresponded with known activity of natural enemies in Oregon (Gent et al 2009). Cooperating growers were asked to avoid using broad-spectrum insecticides to conserve natural enemies, although given the practicalities of commercial crop production this request was not followed in all cases.…”
Section: Experimental Design and Treatment Applicationmentioning
confidence: 99%
“…Management required to minimize crop damage from powdery mildew involves the application of multiple fungicide chemistries, each with varying levels of effects on nontarget organisms (James and Coyle 2001;Mahaffee et al 2003;Gent et al 2008Gent et al , 2009Woods et al 2012).…”
mentioning
confidence: 99%